Prime Time. - Andriesse, Paul; Derks, Hans; Derks, Sandra; Feigl, Franz; Frankenhuizen, Arthur; Giele, Peter; Hoek, Els; Houweling, Jos; Klashorst, Peter; Malasch, Rob; Zwagerman, Joost; de Jong, Ad; et al. (Amsterdam : W139, 1989)
van den Ban, Hans ; Boodt, Annelies ; Botma, Akke ; Brasser, Floris ; van Buren, Ad ; Derks, Iris ; Derks, Jeroen ; Dragstra, Harry ; Durlacher, Eva ; De Vier Evangelisten ; Feddema, Thomas ; Gronheid, Lies ; Grubben, Brigitte ; Jarvis, Steve ; de Jong, Ad ; de Jong, Niek ; Van Kerckhoven, Anne-Mie ; Klinkenberg, John ; Lancel, Arjen ; de Leeuw, Hans van ; de Leij, Gosse van ; Meyers & Berkowitz, Ronald & Gershon ; López, Elvis ; de Moor, Robert ; Neve, Arthur ; Oudendijk, Sonja ; van Baarda, Linda ; Busscher, Jeroen ; Evers, Rudy ; Hem, Laurens du ; Hey, Jozef ; Hille, Paulien ; Hoksbergen, Christel ; Hoyng, Femke ; Kool, Renée ; Meekel, Jurgen ; Mohr, Thomas ; de Poel, Beatrice van ; Roodenburg, Simcha ; Sleegers, Erwin ; Thijssen, Tony ; Voet, Michiel ; Woutersen, Jaqueline ; Zwart, Monica ; van Roij, Jos ; Santfort, Tom ; Schouwenberg, Louise ; Smit, Titia ; Speckens, Han ; Staal, Niels ; Thijssen, Tony ; Tolsma, Frank ; Verburg, Jan M. ; Vulto, Jos ; de Wijs, Albert ; Zondag, Ans
Jaaroverzicht Prime Time : 1ste tent. : 1989-02-23 tot 1989-02-26, laatste tent. : 1989-11-25 tot 1989-12-16
Nederlands & Engels
boek